2004
DOI: 10.1111/j.1365-3040.2003.01151.x
|View full text |Cite
|
Sign up to set email alerts
|

Isoprenoid emission in trees of Quercus pubescens and Quercus ilex with lifetime exposure to naturally high CO2 environment

Abstract: The long-term effect of elevated atmospheric CO 2 on isoprenoid emissions from adult trees of two Mediterranean oak species (the monoterpene-emitting Quercus ilex L. and the isoprene-emitting Quercus pubescens Willd.) native to a high-CO 2 environment was investigated. During two consecutive years, isoprenoid emission was monitored both at . Long-term exposure to high atmospheric levels of CO 2 did not significantly affect the actual isoprenoid emissions. However, when leaves of plants grown in the control sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
74
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(79 citation statements)
references
References 63 publications
5
74
0
Order By: Relevance
“…Moreover, they appear also to depend on light and temperature levels experienced by the plant in the previous hours, days or even weeks. The dependence on temperature during previous days or weeks has been observed in the case of isoprene (Monson et al, 1994;Sharkey et al, 1999;Pétron et al, 2001;Rapparini et al, 2004) and 2-methyl-3-buten-2-ol (MBO) (Gray et al, 2003(Gray et al, , 2006. This dependence is apparently due to changes in the concentration of enzymes responsible for the production of these compounds (Schnitzler et al, 1997) and is consistent with their hypothesized role as thermal protectant (Sharkey et al, 2008).…”
Section: Introductionsupporting
confidence: 59%
“…Moreover, they appear also to depend on light and temperature levels experienced by the plant in the previous hours, days or even weeks. The dependence on temperature during previous days or weeks has been observed in the case of isoprene (Monson et al, 1994;Sharkey et al, 1999;Pétron et al, 2001;Rapparini et al, 2004) and 2-methyl-3-buten-2-ol (MBO) (Gray et al, 2003(Gray et al, , 2006. This dependence is apparently due to changes in the concentration of enzymes responsible for the production of these compounds (Schnitzler et al, 1997) and is consistent with their hypothesized role as thermal protectant (Sharkey et al, 2008).…”
Section: Introductionsupporting
confidence: 59%
“…that emit mainly isoprene (Kesselmeier and Staudt 1999). The blend produced by holm oak has been studied mainly in relation to its modulation by abiotic factors (temperature, light, drought, different CO 2 concentrations) (Staudt and Bertin 1998;Llusia and Peñuelas 1999;Rapparini et al 2004;Peñuelas and Staudt 2010). In accordance with previous reports of holm oak terpene emissions, we found that the blend produced by holm oak saplings was composed mainly of α-and β-pinene, sabinene and myrcene (Street et al 1997;Staudt and Bertin 1998).…”
Section: Discussionsupporting
confidence: 74%
“…It is interesting to observe that many exper iments in which the inhibition of isoprene by elevated CO2 was not observed, were based on branch enclosure long-term measure ments (e.g., Rapparini et al 2004). We there fore also put forward the suggestion that branch enclosures strongly and independent ly affect many physiological features, and do not offer representative indications of the ac tual impact of elevated CO2 on primary and secondary carbon metabolism in nature.…”
Section: Discussionmentioning
confidence: 98%